An Exploratory Study of Shari'ah Issues in the Application of Tabarru' for Takaful - M. Mahbubi Ali; Rusni Hassan; Shabana M. Hasan (Global Review of Islamic Economics and Business, 2014)
Takaful industry has witnessed an exponential growth across the world over the last decade, demonstrating an enormous demand for takaful products ranging from short-term general takaful to long-term family takaful. It has attracted considerable attention not only from the Muslim countries, but also from the non-Muslim countries. Despite its promising growth, however, the takaful industry continues to face numerous contentious Shari'ah issues. The present study aims to discuss some of the most fundamental Shari'ah issues in takaful, namely the issue of applying tabarru' concept in takaful and the issue of underwriting surplus of tabarru' fund.